Complement-mediated, infection-enhancing antibodies in plasma from vaccinated macaques before and after inoculation with live simian immunodeficiency virus. - Montefiori, D C (1990)
Rhesus monkeys vaccinated against infection with simian immunodeficiency virus (SIV) were examined, in retrospect, for the presence of infection-enhancing antibodies and possible consequences associated with the presence of these antibodies. At the time of experimental inoculation with live virus, complement-mediated, infection-enhancing antibodies were detected in plasma specimens from six of six animals vaccinated with detergent-inactivated whole virus, from nine of nine animals vaccinated with Formalin-inactivated whole virus, and from seven of eight animals immunized with two SIV subunit preparations. The presence of infection-enhancing antibodies at the time of viral challenge gave no indication of predicting vaccine success or failure. After live-virus challenge, titers of infection-enhancing antibodies, like enzyme-linked immunosorbent assay titers, increased in unprotected animals and decreased or became undetectable in animals protected by vaccination. Thus, vaccine protection against SIV infection can still be achieved in the presence of detectable complement-mediated, infection-enhancing antibodies.